2019
DOI: 10.1186/s12917-019-2056-9
|View full text |Cite
|
Sign up to set email alerts
|

Malarone® induced pancreatitis and alopecia in a dog: a case report

Abstract: Background Malarone ® is a drug used for the treatment of malaria in humans. This drug is also particularly effective in the treatment of canine Babesia gibsoni infections. Malarone ® is rarely used in dogs, and its adverse effects have not been widely reported. Its mechanism of action is related to the inhibition of cytochrome b and electron transport in the cell. This is the first known report of the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…High fat diet [2][3][4] Ingestion of unusual food items 5,6 Ingestion of table scraps 5 Ingestion of trash 5 Drugs/toxins L-asparaginase 7,8 Phenobarbital and potassium bromide 9-11a Azathioprine [12][13][14] Potentiated sulfonamides 15 Organophosphates 12,16 Corticosteroids, 12,17b Furosemide 12 Atovaquone/proguanil (Malarone) 18 N-methyl-glucamine (Meglumine), 19b…”
Section: Dietary Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…High fat diet [2][3][4] Ingestion of unusual food items 5,6 Ingestion of table scraps 5 Ingestion of trash 5 Drugs/toxins L-asparaginase 7,8 Phenobarbital and potassium bromide 9-11a Azathioprine [12][13][14] Potentiated sulfonamides 15 Organophosphates 12,16 Corticosteroids, 12,17b Furosemide 12 Atovaquone/proguanil (Malarone) 18 N-methyl-glucamine (Meglumine), 19b…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Potentiated sulfonamides, furosemide, clomipramine, atovaquone/ proguanil (Malarone), and n-methyl-glucamine (Meglumine) are associated with the development of AP in isolated dogs. 12,15,[18][19][20] Another prospective study reported that none of 20 dogs treated with meglumine and allopurinol developed increased cPLI concentrations or clinical signs consistent with pancreatitis. 78 Isolated reports of toxins such as zinc causing AP have been reported.…”
Section: Drugs/toxinsmentioning
confidence: 99%